The barf of the bedazzler - Reynolds, Aaron, 1970- (Reynolds, Aaron, 1970- Fart quest (Series), 2021)
"After crushing their very first quest, young adventurers Pan, Moxie, and Fart are hungry for their next challenge. Luckily, the Great and Powerful Kevin has cooked up something for the trio: Locate a bedazzler--a rare and monstrous creature of truly horrific power--and bring back . . . its barf"--